Perbandingan Tingkat Kepercayaan Peserta Didik Suku Banjar Terhadap Konselor Dan Guru Spiritual (Studi di SMAN 3 Martapura) - Nisa Budi Yani (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
The client's trust in the counselor to be open in telling the problem, the client's willingness to come to the counselor, and the client's perception that this does not make the counselor a threat. Likewise, a spiritual teacher who can be trusted (trustworthiness) refers to things that are suggested by the teacher to be done voluntarily by the Banjar community without any coercion. This study aims to analyze the level of trust of students in spiritual counselors and teachers in the aspect of alleviating problems as well as carry out a comparative correlation analysis on comparisons or differences in the level of trust of students in counselors and spiritual teachers at SMAN 3 Martapura. The results of this study show that the independent simple t test has the difference between counselors (80.542 to 2.920) and spiritual teachers (81.970 to 1.492). 95% Confidence Interval of the Difference. The resultof Sig. "Levene's Test for Equality of Variances" of 0.000 for counselors and spiritual teachers. Thus, the significant difference between students' trust in counselors and significant differences between students' trust in spiritual teachers does not make students lose their way, students will choose who to trust in helping to alleviate their daily problems.Keywords:Counselors,Learners, Spiritual Teachers.